WAYANG SULUH AS A LEARNING MEDIA IN TEACHING HISTORY IN HIGH SCHOOL - Utomo, Cahyo Budi; Amin, Syaiful; Ria, Tiara Nove (Paramita: Historical Studies Journal, 2018)
There is no doubt that in the process of learning history in schools, the role of the media is very important and strategic. Many media can be developed by utilizing what is already around the community, one of which is wayang suluh. Utilizing wayang suluh as historical learning media is expected to optimize the process and the learning result of history. It also can introduce their own culture that contains the value of wisdom in learners. Based on field studies, the need for alternative media learning history is quite high (87.5%). Most (75%) of the research respondents were very enthusiastic with the concept of learning media of wayang suluh. It is believed that the concept of wayang suluh makes learning more interactive because it involves all class participants to interact. Based on the results of the feasibility test (validation) by media and material experts, with the suggested improvements and additions, the puppet as a medium of learning history, declared good or feasible to be used as a medium of learning history in high school .Ã‚Â Tidak ada keraguan bahwa dalam proses belajar sejarah di sekolah, peran media sangat penting dan strategis. Banyak media dapat dikembangkan dengan memanfaatkan apa yang sudah ada di sekitar masyarakat, salah satunya adalah wayang suluh. Pemanfaatan wayang suluh sebagai media pembelajaran sejarah diharapkan bisa mengoptimalkan proses dan hasil belajar sejarah. Ini juga bisa mengenalkan budaya mereka sendiri yang berisi nilai kebijaksanaan pada peserta didik. Berdasarkan studi lapangan, kebutuhan akan pembelajaran media pembelajaran alternatif cukup tinggi (87,5%). Sebagian besar (75%) responden penelitian sangat antusias dengan konsep media pembelajaran wayang suluh. Diyakini bahwa konsep wayang suluh membuat belajar lebih interaktif karena melibatkan semua peserta kelas untuk berinteraksi. Berdasarkan hasil uji kelayakan (validasi) oleh pakar media dan material, dengan saran perbaikan dan penambahan, wayang sebagai media pembelajaran sejarah, dinyatakan baik atau layak dijadikan media pembelajaran sejarah di SMA.Ã‚Â